Characteristics of Chemistry Teaching Material Voltaic Cells on Students’ Creativity and Concept Mastery - Giyanto Giyanto; Bibin Rubini; Leny Heliawati (Universitas Syiah Kuala, 2020)
This study aims to find the characteristics of chemistry teaching material used by 16 teachers on the concept of voltaic cells in vocational high schools. The characteristics of teaching material accommodate 21st-century learning which includes the accuracy of the contents, the accuracy of the scope, the updating of the material, the comprehensibility of the text, the use of the language, and the use of the illustrations. The research identifies student competency profiles that are indispensable in 21st-century learning, namely creativity and concept mastery. The subject of the research is teaching material used by 16 chemistry teachers in 16 vocational high schools with 95 students studied. Data were collected using observation sheets, product creativity questionnaires, and tests of students' concept mastery. The data obtained were analyzed using a quantitative descriptive method. The results show that the teaching materials used in learning had not used an approach that encouraged creativity and learning outcomes for students. This resulted in low creative-thinking ability at a rate of 27.03% and in low mastery concept showed from the mean of learning outcomes at a score of 22.4 from a maximum score of 100. The study concludes that the characteristics of chemistry teaching material voltaic cells are not under the demands of the characteristics of 21st-century learning in the aspect of the content.